Pandemics, prophecies and autonomies: the Guarani and Kaiowá against the COVID-19 - Johnson, Felipe Mattos; Faria, Lucas Luis (Cadernos de Campo (São Paulo, 1991), 2020)
This report, through an engaged anthropology and a critical psychology, articulates Guarani and Kaiowá narratives with the new coronavirus pandemic in order to emphasize the autonomous actions of the indigenous population to restrain the dissemination of COVID-19 in their territories. On the other hand, the first cases of infection amongst the Guarani and Kaiowá in Mato Grosso do Sul emerge through large agribusiness companies, precisely the sector that is responsible for a considerable part of habitat destruction, what creates frictions between human and non-human beings, generating proto-pandemic situations. In this regard, we seek to demonstrate the continuity of coloniality through the contradiction between the non-indigenous way of life and the sensibility of the world according to the Guarani and Kaiowá. The objective is to decolonize speeches about health and disease, highlighting the political agency of the indigenous people to face the pandemic.